KONSTRUKSI DISKURSIF TUJUAN PADA TEKS PAKET PERJALANAN WISATA PADA WEBSITE BIRO PERJALANAN WISATA - I Gusti Ngurah Adi Rajistha; Dewa Ayu Kadek Claria; Kuntayuni (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
The website of the travel agency has pictures and texts to promote the services offered. In the text of the tour package offered, some sentences express certain purposes to describe the tour package offered. This article aims to describe the discursive construction of purpose used in the text of the tour package. This research is descriptive qualitative research in which the data source of this research is the tour package texts of ganggabali.com. The kind of data used is sentences found in the tour package texts. The research instrument used is antconc to collect the data. The texts are saved in the *.txt format to make the data collection by using antconc easier. The data that have been collected and classified were analyzed by using the theory of discursive construction of purpose proposed by Leeuwen. The data we analyzed by considering the kinds of the discursive construction of purpose. In this case, the elements that determine the discursive constructions were analyzed first. There were three steps in analyzing the data, namely the analysis of goal orientation, means orientation, and effect orientation in the sentences showing the function of discursive constructions to describe the purpose. The result of this research shows that all the orientations of discursive constructions of purpose were applied in the texts of the travel agency website. Keywords: discourse analysis; discursive construction of purpose, website of travel agency